A Systematic Review and Network Meta-Analysis on the Efficacy of Medications in the Treatment of Chronic Idiopathic Constipation in Japan. (30th November 2021) - Nakajima, Atsushi; Shoji, Ayako; Kokubo, Kinya; Igarashi, Ataru
Abstract : Background . In the 2010s, medications with new mechanisms were introduced in Japan for the treatment of chronic idiopathic constipation (CIC). A few systematic reviews have compared medications' relative efficacy, but the reviews included studies on patients from various races, even though the mechanism of CIC is considered to differ between races. The aim of this study was to use a systematic review and network meta-analysis to compare the relative efficacy of these medications in Japanese patients. Methods . We conducted a meta-analysis and report it here according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We identified studies by searching MEDLINE (via the PubMed interface) and the Cochrane Library and ICHUSHI databases and included randomized clinical trials that compared medications for CIC with placebo in Japanese adults. Two reviewers independently screened and assessed articles, abstracted data, and assessed the risk of bias. We pooled data by random-effects meta-analyses and also performed a Bayesian network meta-analysis to indirectly compare data. Results . The present systematic review and meta-analyses included 1460 patients in 6 randomized clinical trials: 2 on linaclotide, 3 on elobixibat, 2 on lubiprostone, and 1 on lactulose. The results of direct comparisons showed that linaclotide, elobixibat, and lubiprostone were superior to placebo in the change of spontaneous bowel movements (SBMs) within 1 week: linaclotide, 1.95 (95% CI, 1.51-2.39); elobixibat, 5.69 (95% CI, 3.31-8.07); and lubiprostone, 2.41 (95% CI, 0.82-4.01). The Bayesian network meta-analysis showed consistent results. Elobixibat 10 mg was ranked first for the increase in SBMs and complete SBMs within 1 week and the time to first SBM. Lubiprostone 48  μ g was ranked first for the proportion of patients with SBM within 24 hours. Conclusion . Our direct and indirect meta-analyses revealed that the new CIC medications available in Japan have equal efficacy but that elobixibat and lubiprostone are highly likely to be more efficacious.